Solar hydrogen production and storage techniques - Tassou, Savvas A.; Kalogirou, Soteris A.; Panayiotou, Gregoris (My University, 2010)
The main disadvantage of Renewable Energy Sources (RES) systems is their variability and dependence on environmental conditions. This problem can be overcome by storing energy in the form of hydrogen either for long or short term. One of the most promising types of such systems is the solar hydrogen energy system (SoHyS) where essentially the electricity produced by the PVs is stored in the form of hydrogen by using a variety of storage methods and means. The hydrogen can be then reconverted to electricity on demand by using a fuel cell. In this work a brief description of SoHyS and their characteristics is presented along with recent patents on some of the main system components such as the electrolyser and the storage techniques and devices. The future trends of research in this area would be on more efficient electrolysers and more advanced and lightweight storage media in order to increase the overall effectiveness of the system
Keywords: Hydrogen--Storage; Fuel cells; Hydrides; Solar energy